Lambda Nachrichten : Zeitschrift der Homosexuellen Initiative Wien. (Wien : HOSI, 1980)
Fonds Suzan Daniel (FSD)
Periodiciteit : driemaandelijks
Redactie : Pf 22, 1037 Wien ; vanaf (1982) 3 : Novaragasse 40, 1020 Wien
Duits
Periodiek